Kualitas Semen Beku Kambing Peranakan Etawa yang Dikriopreservasi Menggunakan Pengencer Tris Kuning Telur dengan Penambahan Ekstrak Bunga Rosella - Huda, Ahmad Aly; Wahdi, Anis; Rahmat, Rahmat; Syarifuddin, Nursyam Andi; Rizal, Muhammad (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2025)
This study aimed to evaluate the effect of adding roselle (Hibiscus sabdariffa L.) flower extract to Tris-egg yolk extender on the post-thaw motility and viability of frozen semen from Etawah crossbred (PE) goats. The research was conducted from April to June 2025 at the Abadi Maju Farmers Group and the Animal Reproduction Laboratory, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. Semen was collected from four PE goat bucks and diluted with Tris-egg yolk extender supplemented with roselle extract at concentrations of 0% (P0/control), 1% (P1), 3% (P2), and 5% (P3). The study used a completely randomized design with four replications per treatment. Data were analyzed using ANOVA or Kruskal-Wallis test depending on data distribution. The results showed that the addition of roselle extract had no significant effect (P>0.05) on post-thaw motility or viability. However, descriptively, P2 (3%) exhibited the highest motility (47.50%) and viability (52.00%) compared to other treatments. These findings suggest that supplementation with 3% roselle extract in Tris-egg yolk extender tends to better preserve the motility and viability of frozen semen in PE goats. Further research is needed to optimize the concentration and evaluate its effect on fertility.